Reinterpreting Springwells Ceramics in the Great Lakes Region of North America. Issue 2 (4th May 2019) - Carroll, Jon W.
ABSTRACT: The original ceramics typology developed for Younge/Western Basin Tradition Springwells phase (ca. AD 1160–1420) assemblages included three variants known as Macomb Linear, Macomb Interrupted Linear, and Springwells Net Impressed ceramics. This discussion considers how subregional variation in Springwells decorative styles reflects participation in a larger regional social network.